Factores que participan en la dinámica entre el financiamiento y los comerciantes de indumentaria del Centro Comercial de la Ciudad de Loja. - Ortiz Uchuari., Jessica Alejandra (2024)
Financing is a mechanism for providing funds to natural or legal persons, it is the main factor of success in which includes resources needed to start any project. There are two types of financing: formal financing is provided by financial institutions that are regulated and supervised by the government, and informal financing refers to funds obtained through unregulated channels provided by moneylenders, family and friends. Therefore, the following objective has been set: to determine the factors that influence access to financing for apparel merchants in the Loja Shopping Center. The research had a mixed qualitative and quantitative approach, which was used for the application of the survey to the merchants and the tabulation of the results. To complement the research work, the deductive method was used to develop the theoretical framework, the inductive method was used to analyze the characteristics of the merchants, the analytical method was used to examine the reality of access to financing and the synthetic method helped to summarize the work to extract the most relevant information. The results obtained show that 65% of the merchants turn to informal financing due to the requirements and only 35% turn to formal financing; therefore, it is concluded that there is a greater participation of usury due to the agility in the delivery of the money and the ease of payment granted to the merchants.